Transverse colon xanthoma: Rare yet important - Sameer Ahmed Ansari; Ejaz Waris; Omar Sharif; Lamma Alghiryafi (Saudi Journal for Health Sciences, 2019)
Colonic xanthomas are rare, benign lesions of the gastrointestinal tract characterized by a foamy cell containing lipid in the lamina propria and mucosa. They have been commonly described in the stomach and rectosigmoid region in few case reports. Their association with adenoma and adenocarcinoma had made them a visible indicator of malignancy. Hence, a thorough investigation and follow-up of the patient are mandatory to search for such lesions.